Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae) - Nekhaev, Ivan O. (Zootaxa, 2018)
Five species of the family Cancellariidae are currently known from Arctic seas: Admete contabulata Friele, 1879, A. clivicola Høisæter, 2011, A. solida (Aurivillius, 1885), A. viridula (Fabricius, 1780) and Iphinopsis inflata (Friele, 1879) (Golikov et al. 2001; Kantor & Sysoev 2006; Høisæter 2011). Admete contabulata, A. clivicola and Iphinopsis inflata are only known from the Atlantic part of the Arctic, i.e. Norwegian and southwestern Barents seas (Høisæter 2011; Nekhaev 2014). Admete solida has been rarely reported since its first description from the Bering Strait (Sysoev & Kantor 2002), however Nekhaev & Krol (2017) recently reported a specimen from the eastern region of the Barents Sea that is similar in morphology to the holotype of this species. Admete viridula is the only representative of Admete reported from Siberian seas (Golikov et al. 2001; Lyubin 2003; Kantor & Sysoev, 2006).